G180(P) Exploring equity, patient experience and engagement in paediatric sickle cell disease (SCD): a quality improvement project. (25th October 2020) - Huckerby, L; Lynch, H; Clubb, R; Haddock, G; Turner, K; Basnett, I; Leigh, A
Abstract : Aims: To evaluate paediatric SCD patient experiences of outpatient, inpatient and emergency services at a district general hospital To understand the factors contributing to a 20% rate of missed clinic appointments for SCD To implement changes to paediatric SCD services that improve outpatient clinic attendance and patient experiences Methods: Primary data were collected from June 2018 to August 2019, through the following: Semi–structured questionnaire with patients and carers Qualitative interviews with patients and carers after missed clinic appointments Audit (SCD Acute Pain Management Audit) of NICE guidance (CG143) Statistical Analysis of Index of Multiple Deprivation (IMD) for all SCD patients, those who missed clinic appointments, and those attending A&E Results: Semi-structured questionnaire (n=12): 66% of patients presented to A&E for urgent treatment rather than GP or home treatment 33% had needed emergency treatment in the last 6 months 60% of patients stated their pain was treated quickly in A&E (40% not quickly enough) 30% felt A&E staff did not know enough about SCD Qualitative interviews (n=5): Reasons given for missing appointments included: too many appointments, financial difficulties, travel difficulties, unwell child, appointments booked too far in advance Suggestions from families to improve appointment attendance included to send a closer reminder and to follow up telephone confirmations with a letter SCD Pain Management Audit (n=28): Pain was assessed using an age appropriate scoring tool in 89% of cases We offered analgesia within 30 minutes in only 46% of cases 73% were prescribed laxatives when on opioids, and 47% were prescribed anti–emetics or anti–pruritics Statistical Analysis (n=5190): Preliminary analysis has shown: Using the IMD of residence, the most deprived (groups 1–3) had higher rates of missed hospital appointments when compared to groups 4–8 An increased rate of admission was observed if at least one outpatient appointment was missed Conclusion: Higher rates of missed appointments were observed in the most deprived groups and correlated with increased admissions. Financial difficulties may contribute to missing hospital appointments, adding to health inequities in this vulnerable group. The next phase will include implementing changes to improve paediatric care and accessibility, including considering virtual or community clinics.